Analysis of Student Responses to STEM-Inquiry Learning Using Cloud Classroom (CCR) on Food Loss and Food Waste Topics - Ernita Vika Aulia; Martini Martini; Siti Nurul Hidayati; Beni Setiawan; Dyah Astriani (Jurnal Penelitian Pendidikan IPA, 2023)
The implementation of STEM-Inquiry learning puts forward the process of how students independently acquire knowledge through problem solving and have the ability to use that knowledge. STEM-Inquiry learning supported by the use of the CCR platform can support online learning activities, allow students to work in groups, and help students not only memorize concepts, but can understand and apply the acquired knowledge in everyday life. This study aims to determine student responses to the application of STEM-Inquiry learning on the topic of food loss and food waste. This research is a quantitative descriptive study using a survey method. The subjects of this study were students of Science Education Class of 2019 State University of Surabaya. The research instrument used was a questionnaire form. The questionnaire form provided consisted of 20 questions developed from 7 indicators, namely interest, novelty, convenience, clarity, interest, assessment, and response. The results showed that the average percentage of student questionnaire responses was 84.9% which was categorized as very positive, meaning that students had an interest and were interested in being involved in a meaningful learning experience. Based on this, it can be concluded that the application of STEM-Inquiry learning on the topic of food loss and food waste received a very positive response from students